Upaya Pencegahan Pernikahan Dini melalui Program Kuliah Kerja Lapangan (KKL) dengan Pendekatan Participatory Action Research di Desa Pangirkiran Dolok - Erwin Hamonangan Pane; Ismali Nasution; Irma Sari Daulay; Era Mutiah; Fitri Rosina; Holila Azaria; Ananda Syahputra; Nabil Nuralfiansyah (Jurnal Transformasi Pendidikan Indonesia, 2025)
Early marriage remains a complex issue in many rural areas of Indonesia, including Pangirkiran Dolok Village. This practice often hinders access to education, disrupts reproductive health, and limits the future potential of adolescents, especially women. To answer this challenge, a Field Lecture Work (KKL) program was implemented with a Participatory Action Research (PAR) approach, which places the community as an active subject in the process of social change. The focus of this activity is to build collective awareness and strengthen the role of citizens in preventing early marriage through participatory education and community empowerment. The methods used included participatory observation, interviews with community leaders, focus group discussions (FGDs), and training and educational campaigns involving adolescents, parents and local stakeholders. The results showed an increase in community understanding of the impact of early marriage and the growth of local initiatives, such as the formation of a youth education group and a community dialog forum. The impact of this activity is not only seen in the change in attitudes towards the practice of early marriage, but also in the emergence of a collaborative spirit in creating a more supportive environment for adolescent development. The PAR approach has proven effective in facilitating social change based on awareness, local values and active community participation.